Caddisflies (Trichoptera) and diatoms of some springs in the vicinity of Łódź (Central Poland) - Kwiatkowska, Katarzyna; Żelazna-Wieczorek, Joanna; Ziułkiewicz, Maciej; Majecki, Janusz (Zootaxa, 2016)
The distribution, species richness and ecology of Trichoptera, the diversity of benthic diatoms, and hydrochemical data in 7 springs in the vicinity of Łódź were investigated in 2011. In total, 17 Trichoptera taxa and more than 300 diatom taxa were collected from the studied springs. Trichoptera and especially diatom taxa are very sensitive indicators of ecological conditions; both showed a strong response to degradation in lowland springs. On the basis of faunal, diatom microfloral, and hydrochemical data, the typology of springs of the vicinity of Łódź is proposed. Two groups of factors (differentiating and non-differentiating) which contribute to distinguishing the studied springs are described. Additional experiments and observations were done on Trichoptera, including their life cycles, biology, and larval diet. In particular, the abundance of common diatom taxa in the guts of Silo sp. larvae was investigated.